Produção de bioetanol a partir de resíduos lignocelulósicos por fermentação em estado sólido - Canabarro, Nicholas Islongo (2015)
The energy crisis caused by the exhaustion of fossil fuels and environmental problems has caused concerns of researchers and, consequently, causing them to seek alternatives to replace fossil fuels with renewable sources. An interesting alternative is the use of solid-state fermentation for biofuels production using agricultural residues as a source of fermentable sugars. In Rio Grande do Sul, about 10 million tons of rice a year are produced in the state, producing around 3 million tons of rice husk and 1.5 million tons of rice bran. Such wastes have great potential for the production of bioethanol, but there are no proper techniques to date for the industrial production of ethanol by these wastes. The ethanol extraction technique from the solid state fermentation process is techniques should be improved so that the process becomes efficient and environmentally friendly. Thus, in this work was carried out a preliminary step to ethanol production process by solid state fermentation, evaluating an ethanol extraction method using distilled water as solvent. In this step, we evaluated parameters influencing the fermentation process (moisture content and initial concentration of ethanol) and the extraction process (temperature, agitation and solid-liquid ratio). Set the extraction conditions, the experimental design methodology was used in order to identify the significant variables in the process of solid state fermentation for ethanol production through the application of a design Plackett & Burmann experiments. The response surface methodology was used to perform process optimization, based on the evaluation of a central composite rotational design (CCRD). For end a scale-up of the simultaneous saccharification and solid state fermentation process was proposed, reaching a final ethanol concentration of 143.88 g EtOH / kg substrate.